Ursolic Acid Hydrazide Based Organometallic Complexes: Synthesis, Characterization, Antibacterial, Antioxidant, and Docking Studies - Jabeen, Muafia; Ahmad, Sajjad; Shahid, Khadija; Sadiq, Abdul; Rashid, Umer (Frontiers in Chemistry, 2018)
In the current research work,eleven metal complexes were synthesized from the hydrazide derivative of ursolic acid. Metal complexes of tin, antimony and iron were synthesized and characterized by FT-IR and NMR spectroscopy. The antibacterial and antioxidant activities were performed for these complexes, which revealed that the metal complexes synthesized are more potent than their parent compounds. We observed that antioxidant activity showed by triphenyltin complex was significant and least activity have been shown by antimony trichloride complex.The synthesized metal complexes were then evaluated against two Gram-negative and two Gram-positive bacterial strains. Triphenyl tin complex emerged as potent antibacterial agent with MIC value of 8 μg/ml each against Shigellaspp, S. typhi and S. aureus. While, the MIC value againstS. pneumoniae is 4 μg/ml.Computational docking studies were carried out on molecular targets to interpret the results of antioxidant and antibacterial activities. Based on the results, it may be inferred that the metal complexes of ursolic acid are more active as compared to the parent drug and may be proved for some other pharmacological potential by further analysis.